THE IMPACT OF WORK–LIFE BALANCE ON EMPLOYEE PERFORMANCE: A SYSTEMATIC REVIEW - Oedi Niesya Bella Ragazza; Erik Irmansyah (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Work-Life Balance is an individual’s ability to maintain equilibrium between work demands and personal life. An imbalance between these aspects can lead to stress, fatigue, and decreased motivation, which negatively affect employee performance. Based on a systematic review of 10 selected journals from a total of 135 reviewed studies, it was found that Work-Life Balance has a positive influence on employee performance. Most studies show that employees who can maintain a good balance between work and personal life tend to have higher job satisfaction, stronger organizational commitment, and increased productivity. Work-Life Balance also helps reduce stress and improve focus at work. Therefore, maintaining a balance between work and personal life is an essential factor in enhancing employee performance and overall well-being.